1980
DOI: 10.1080/00337578008209157
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of defect cluster annealing in semiconductors

Abstract: The change of the potential barrier height Acp at the boundary of the matrix and defect clusters introduced by the highenergy particle irradiation in the course of isothermal annealing is analyzed. It is found, that A 9 is independent of the matrix doping level and is determined by the energy position of defect levels in the core and their concentrations only. The relations describing the change in Acp during isothermal annealing of the defects in the core for the first-and the second-order reactions are obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Based on the observation of the large difference between its thermal and optical ionization energies, the deep donor is attributed to an arsenic interstitial related with a more strained configuration than EL2 [6]. Kolchenko et al observed a defect (which may be identified with EL6), whose emission is strongly dependent on the applied electric field, in g-irradiated GaAs:Te (10 17 cm À3 ); while in electron irradiated material, a defect with a metastable behaviour has been observed [7,8]. Thus the present study is aimed at a systematic investigation on the native defects and their rapid thermal annealing (RTA) induced transformations in Te-doped GaAs through deep level transient spectroscopic (DLTS) studies.…”
Section: Introductionmentioning
confidence: 93%
“…Based on the observation of the large difference between its thermal and optical ionization energies, the deep donor is attributed to an arsenic interstitial related with a more strained configuration than EL2 [6]. Kolchenko et al observed a defect (which may be identified with EL6), whose emission is strongly dependent on the applied electric field, in g-irradiated GaAs:Te (10 17 cm À3 ); while in electron irradiated material, a defect with a metastable behaviour has been observed [7,8]. Thus the present study is aimed at a systematic investigation on the native defects and their rapid thermal annealing (RTA) induced transformations in Te-doped GaAs through deep level transient spectroscopic (DLTS) studies.…”
Section: Introductionmentioning
confidence: 93%